NLRP6 controls pulmonary inflammation from cigarette smoke in a gut microbiota-dependent manner - Nascimento, Mégane; Huot-Marchand, Sarah; Fanny, Manoussa; Straube, Marjolène; Le Bert, Marc; Savigny, Florence; Apetoh, Lionel; Van Snick, Jacques; Trovero, Fabrice; Chamaillard, Mathias; Quesniaux, Valérie F. J.; Ryffel, Bernhard; et al. (Frontiers in Immunology, 2023)
Chronic obstructive pulmonary disease (COPD) is a major health issue primarily caused by cigarette smoke (CS) and characterized by breathlessness and repeated airway inflammation.NLRP6 is a cytosolic innate receptor controlling intestinal inflammation and orchestrating colonic host-microbial interface. However, its roles in the lungs remain largely unexplored. Using CS exposure models, our data show that airway inflammation is strongly impaired in Nlrp6-deficient mice with drastically less recruited neutrophils, a key cell subset in inflammation and COPD. We found that NLRP6 expression in lung epithelial cells is important to control airway and lung tissue inflammation in an inflammasome-dependent manner. Since gut-derived metabolites regulate NLRP6 inflammasome activation in intestinal epithelial cells, we investigated the link between NLRP6, CS-driven lung inflammation and gut microbiota composition. We report that acute CS exposure alters gut microbiota in both wild type (WT) and Nlrp6-deficient mice and that antibiotic treatment decreases CS-induced lung inflammation. In addition, gut microbiota transfer from dysbiotic Nlrp6-deficient to WT mice decreases airway lung inflammation highlighting an NLRP6dependent gut to lung axis controlling pulmonary inflammation.